Relationships between nematodes, weevils, banana and plantain cultivars and damage - Speijer, P.R.; Budenberg, W.J.; Sikora, R.A. (1993)
Infestation of banana and plantain suckers by nematodes (Pratylenchus good‐eyi, Radopholus similis and Helicotylenchus multicinctus) and weevils (Cosmopolites sordidus) increased with time from establishment in a field of eight different cultivars. There was a strong association between nematode and weevil infestation; suckers infested with nematodes were more than four times more likely to be infected by weevil than suckers without nematodes. Weevil damage, measured by percentage coefficient of infestation (PCI) at harvest of the bunch, was higher on a plantain (cv. Gonja) and on an east African highland cooking banana (cv. Lusumba) than on the sweet and multi‐purpose cultivars. There was a correlation between numbers of male weevils caught in a plot and the mean PCI measured in the plot, but no correlation with female numbers.